Management system for managing P1 and P2 students in counselling unit - Nur Syafiqah, Mohamad Sasudin (2018)
Counselling Unit is very important for an educational organization. Counselling Unit of Universiti Malaysia Pahang(UMP) is the organization that responsible for helping students in solving academic, personal, psychosocial and career issues individually and in groups. Counselling Unit of UMP still uses the manual method in managing students especially students of Pemulihan 1 (P1) and Pemulihan 2 (P2). The main problems face is the difficulty in managing student data manually, scheduling session manually which contributes to errors in recording. In managing P1 and P2 students, the Counselling Unit needs to go through the time-consuming procedures and requires more work from counsellors and Staff of Unit Counselling. P1 and P2 student management system is geared towards making all the manual process becomes more effective for the counsellors and students of P1 and P2. The users of the system are UMP Counselling Unit Staffs, counsellors, faculty administration staffs and P1 and P2 students. This system focuses not only on the scheduling of counselling sessions, but data management, generating report, attendance management and all matters related to P1 and P2 students. This system has been developed according to the Rapid Application Development methodology (RAD). The system follows four phases used by RAD methodology. The system tested by counsellor and the system fulfilment all the requirements given.